Stochastics of Cellular Differentiation Explained by Epigenetics: The Case of T‐Cell Differentiation and Functional Plasticity. (12th September 2017) - Bhat, J.; Helmuth, J.; Chitadze, G.; Kouakanou, L.; Peters, C.; Vingron, M.; Ammerpohl, O.; Kabelitz, D.
Abstract: Epigenetic marks including histone modifications and DNA methylation are associated with the regulation of gene expression and activity. In addition, an increasing number of non‐coding RNAs with regulatory activity on gene expression have been identified. Alongside, technological advancements allow for the analysis of these mechanisms with high resolution up to the single‐cell level. For instance, the assay for transposase‐accessible chromatin using sequencing (ATAC‐seq) simultaneously probes for chromatin accessibility and nucleosome positioning. Thus, it provides information on two levels of epigenetic regulation. Development and differentiation of T cells into functional subset cells including memory T cells are dynamic processes driven by environmental signals. Here, we briefly review the current knowledge of how epigenetic regulation contributes to subset specification, differentiation and memory development in T cells. Specifically, we focus on epigenetic mechanisms differentially active in the two distinct T cell populations expressing αβ or γδ T cell receptors. We also discuss examples of epigenetic alterations of T cells in autoimmune diseases. DNA methylation and histone acetylation are subject to modification by several classes of 'epigenetic modifiers', some of which are in clinical use or in preclinical development. Therefore, we address the impact of some epigenetic modifiers on T‐cell activation and differentiation, and discuss possible synergies with T cell‐based immunotherapeutic strategies.